SMEs in the digital era : opportunities and challenges of the digital single market - Carbonara, Emanuela; Tagliaventi, Maria R. (Edward Elgar Publishing, 2023)
"With an interdisciplinary approach, this book elaborates and discusses the strategic, regulatory and economic scenario that the sponsorship of a European Digital Single Market has been generating for small- and medium-sized companies (SMEs). Encompassing expert innovative analysis of the regulatory framework, economic dynamics and organizational processes, SMEs in the Digital Era highlights the effects these have and the complex process through which SMEs can enter and successfully compete in the digital market. With contributions from international scholars, this insightful book takes a deep dive into the current most relevant debates taking place in management, economics and business law using original evidence from a variety of fields and countries. Chapters offer a fresh look at the new policies and regulatory tools required to meet the challenges of digitalization, reflecting on the effects on employment, competition and organizational processes, and how imbalances can impact the future of the technological revolution. Providing insights into the most advanced and recent research on digital markets, this will be an excellent resource for academics, practitioners, managers and policymakers in fields ranging from organization theory and organizational behaviour to strategy, economic analysis as well as economics and business law"--